Leveraging Controlled-Environment Agriculture to Increase Key Basil Terpenoid and Phenylpropanoid Concentrations: The Effects of Radiation Intensity and CO2 Concentration on Consumer Preference - Walters, Kellie J.; Lopez, Roberto G.; Behe, Bridget K. (Frontiers in Plant Science, 2021)
Altering the radiation intensity in controlled environments (CE) can influence volatile organic compound (VOC) biosynthetic pathways, including those of terpenoids and phenylpropanoids. In turn, the concentrations of these compounds can have a profound effect on flavor and sensory attributes. Since sweet basil (Ocimum basilicum) is a popular culinary herb, our objectives were to 1) determine the extent radiation intensity and carbon dioxide (CO2) concentration influence seedling terpenoid and phenylpropanoid concentrations; 2) determine if differences in phenylpropanoid and terpenoid concentrations influence consumer preference; and 3) characterize consumer preferences to better inform production and marketing strategies. Seeds of basil ‘Nufar’ were sown and placed in a growth chamber with CO2 concentrations of 500 or 1,000 µmol·mol‒1 under radiation intensities of 100, 200, 400, or 600 µmol·m–2·s–1 with a 16-h photoperiod to create daily light integrals (DLIs) of 6, 12, 23, and 35 mol·m–2·d–1. After two weeks, leaves were harvested for evaluation. To determine the concentrations of the terpenoids 1,8 cineole and linalool, and the phenylpropanoids eugenol and methyl chavicol, gas chromatography mass spectrometry (GCMS) analysis was conducted. Consumer sensory panel evaluations were conducted to quantify preferences through Likert scale, open-ended quality attribute, and sensory questions. Overall, increasing radiation intensity from 100 to 600 µmol·m‒2·s‒1 increased 1,8 cineole, linalool, and eugenol concentrations 2.4-, 8.8-, and 3.3-fold, respectively, while CO2 concentration did not influence VOCs. Contrary to our hypothesis, increased VOC concentrations were not correlated with consumer preference. However, overall liking was correlated with aftertaste and flavor. The conclusion that consumer preference is dependent upon flavor can be drawn. However, increasing VOC concentrations to increase flavor did not improve flavor preference. Many consumer sensory preference characteristics (favorable preference for aftertaste, bitterness/sweetness, color, flavor, overall liking, and texture) were correlated with basil grown under a radiation intensity of 200 µmol·m‒2·s‒1. This led us to determine that consumers prefer to detect the characteristic basil flavor made up of 1,8 cineole, eugenol, and linalool, that was not as prevalent in basil grown under 100 µmol·m‒2·s‒1, but too high in basil grown under 400 and 600 µmol·m‒2·s‒1, which led to lower consumer preference.